Second Five-Year Plan Madras State Review of the Progress for First Four Years (1956-57 to 1959-60) and the Programme for the Fifth Year (1960-61) - Planning Commission (Planning Commission, 1956)
It has been rightly said that agriculture which engages about 75 per cent of our population is the main ‘ industry ’ of our country. When the First Five-Year Plan was formulated, the country was faced with a serious shortage of foodgrains and large quantities had to be imported from foreign countries involving a severe drain on the available slender foreign exchange resources. High priority was therefore given in that Plan to Agricultural schemes with the main objective of securing self-sufficiency in food. Madras State achieved an additional production of 5.8 lakh tons of foodgrains during that period, the actual food production recorded in 1955 -56, i.e., the last year of the First Plan being 44.21 lakh tons.
Finance (Planning and Development) Department, Government of Madras